THE IMPLEMENTATION OF CORPORATE GOVERNANCE IN ISLAMIC BANKING IN INDONESIA BASED ON AAOIFI STANDARD - astuti, rahma yudi (Solusi, 2021)
This study aims to analyze the implementation of Corporate Governance in Islamic banking in Indonesia and the implementation of Corporate Governance in Islamic banking in Indonesia according to the standards of Corporate Governance by AAOIFI. This study used secondary data obtained from the annual report of Good Corporate Governance of Sharia Commercial Bank which has been published in 2019. The method used in this study is qualitative with the type of research is content analysis from the annual Good Corporate Governance report of Islamic bank in Indonesia. The results of this study indicate that the implementation of Corporate Governance at Sharia Commercial Banks in general have done good corporate governance which is marked with the result of self-assessment of every Sharia Commercial Bank which on average gets a good predicate. The results of research on the implementation of AAOIFI standards of Corporate Governance in general have applied some of the AAOIFI standards, but there is one standard AAOIFI that has not been applied by Sharia Commercial Banks other than Bank Muamalat. The standard that has not been applied is Internal Sharia Reviews which should be established in the policy.Keywords: Islamic Banking, Corporate Governance, AAOIFI